PENEGAKAN HUKUM DI INDONESIA - Sanyoto, Sanyoto (Jurnal Dinamika Hukum, 2008)
The law enforcement shall do correctly and effectively to measure the succeed of the state, particularly in giving protection toward the citizen. The state realize that the law enforcement must related with the the five pillars of law instrument which are law builder, law enforcer, people consciousness, culture and infrastructure which supported. Expedient justify with increasing awareness of law society, so the consequence of building still as cut down action and not fait. Kata kunci : penegakkan hukum, perlindungan masyarakat